2019
DOI: 10.1017/s0022029919000323
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibits lipopolysaccharide-induced expression of inflammatory cytokines by suppressing TLR4-mediated NF-ĸB and MAPK signaling pathways in rumen epithelial cells of Holstein calves

Abstract: Subacute ruminal acidosis (SARA) can increase the level of inflammation and induce rumenitis in dairy cows. Berberine (BBR) is the major active component of Rhizoma Coptidis, which is a type of Chinese anti-inflammatory drug for gastrointestinal diseases. The purpose of this study was to investigate the anti-inflammatory effects of BBR on lipopolysaccharide (LPS)-stimulated rumen epithelial cells (REC) and the underlying molecular mechanisms. REC were cultured and stimulated with LPS in the presence or absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
(36 reference statements)
2
17
0
Order By: Relevance
“…Researchers well‐established the correlation between LPS exposure and alterations in lung function tests. [ 31,34 ] Clinically, a pulmonary function test (PFT) has been widely implemented for the early detection and monitoring of pneumonia in patients. [ 35 ] Thus, PFT is considered an important noninvasive tool for the assessment of the functionality of the lung during pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers well‐established the correlation between LPS exposure and alterations in lung function tests. [ 31,34 ] Clinically, a pulmonary function test (PFT) has been widely implemented for the early detection and monitoring of pneumonia in patients. [ 35 ] Thus, PFT is considered an important noninvasive tool for the assessment of the functionality of the lung during pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…4), which suggest that BBR has anti-inflammatory effects mainly through NF-κB deactivation in LPS-exposed mIMCD-3 cells. Some previous researches have reported that BBR inhibits inflammatory mediators and NF-κB signaling in various different disease models (19,(63)(64)(65)(66)(67). However, there is no report that BBR could have anti-inflammatory and protective effects in lPS-exposed inner medullary collecting duct (iMcd) cells.…”
Section: Discussionmentioning
confidence: 99%
“…in previous studies, BBr has been found to be able to inhibit LPS-induced expression of inflammatory cytokines by suppressing the Tlr4-mediated nF-κB and MaPK signaling pathways in rumen epithelial cells (53). BBr was also reported to inhibit aP-1 activity in a dose-and time-dependent manner.…”
Section: Genes Involved In the Tlr4/nf-κb And Mapk/ap-1 Pathwaymentioning
confidence: 79%